Selective Phosphorylation of Akt/Protein-Kinase B Isoforms in Response to Dietary Cues - Trautenberg, Laura Christin; Prince, Elodie; Maas, Cornelia; Beier, Nora; Honold, Freya; Grzybek, Michal; Brankatschk, Marko (Frontiers in Cell and Developmental Biology, 2019)
A calorie-rich diet is one reason for the continuous spread of metabolic syndromes in western societies. Smart food design is one powerful tool to prevent metabolic stress, and the search for suitable bioactive additives is a continuous task. The nutrient-sensing insulin pathway is an evolutionary conserved mechanism that plays an important role in metabolism, growth and development. Recently, lipid cues capable to stimulate insulin signaling were identified. However, the mechanistic base of their activity remains obscure to date. We show that specific Akt/Protein-kinase B isoforms are responsive to different calorie-rich diets, and potentiate the activity of the cellular insulin cascade. Our data add a new dimension to existing models and position Drosophila as a powerful tool to study the relation between dietary lipid cues and the insulin-induced cellular signal pathway.